Assessing Purity in the Halal Poultry Supply Chain: A Case Study of Malaysian Poultry Industries - Lateb, Nadiah Abdul; Jaswir , Irwandi; Kartika, Betania (Journal of Ecohumanism, 2025)
The concept of Halal, deeply rooted in Islamic principles, emphasizes purity alongside hygiene, safety, and quality. Despite stringent regulations in Malaysia’s poultry industry, challenges such as contamination and improper handling persist, raising concerns over religious compliance and consumer trust. This study explores the purity practices in the Malaysian Halal poultry supply chain, focusing on three major industry players. Using a qualitative approach with in-depth interviews and Atlas.ti analysis, the findings reveal industry strengths in purity practices and areas needing improvement. Continuous monitoring, stricter enforcement, and enhanced stakeholder awareness are critical for maintaining Halal integrity. These insights contribute to better regulatory frameworks and consumer assurance in the Halal poultry sector.